Relationship Between social intelligence and resonant leadership in public health Institutions - Marisol del Valle Marcano, Ramineth Joselin Ramírez Molina,; Ramírez Molina, Reynier Israel; Lay Raby, Nelson David; Herrera Tapias, Belina Annery (Opción, 1970)
The investigation sought to establish the relationship between social intelligence and leadership resonant in public health institutions. quantitative methodology, descriptive, field design, transversal and not experimental and correlational, using the survey technique and an instrument a questionnaire of 57 items, aimed at medical staff, care and management of the institutions under review, classified type 4 of the Zulia state. The findings reflect the lack of correlation between the study variables. It is concluded that these are manifested independently, requiring the redefinition of past concepts of social relationships and innovative styles to lead.